2019
DOI: 10.33899/ijvs.2019.153860
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and phylogenetic study of Hyalomma anatolicum in Al-Najaf, Iraq

Abstract: Studies had been previously conducted to genetically identify species of ticks in Iraq. Therefore, the current investigational study was conducted to recognize the species of 50 ticks collected from infested skin of cattle. The current study defined the ticks to be from Hyalomma genus depending on their morphological features. Using mitochondrial cytochrome oxidase subunit  (Cox) gene, 16 ticks were further confirmed using polymerase chain reaction (PCR). Two PCR products were subjected to DNA sequencing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…There was another article supports the same species that found in mountainous areas of Golestan province, Iran by Sarani et al (13). However, this study does not correspond with Al-Fatlawi et al (14), who recorded that Hyalomma spp., were more predominant in the south of Iraq. Molecular study, for the first time this technique has been used in Duhok, Iraq and it's especially for the identification of tick species.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…There was another article supports the same species that found in mountainous areas of Golestan province, Iran by Sarani et al (13). However, this study does not correspond with Al-Fatlawi et al (14), who recorded that Hyalomma spp., were more predominant in the south of Iraq. Molecular study, for the first time this technique has been used in Duhok, Iraq and it's especially for the identification of tick species.…”
Section: Discussionsupporting
confidence: 39%
“…Also sequences of mitochodrial DNA are appropriate for genetic analysis of closely related species. A research was carried out in Iraq by Al-Fatlawi et al (14) using CoxIdependent PCR and defining Hyalomma analoticum.…”
Section: Discussionmentioning
confidence: 99%
“…This tick was identi ed as a vector of Theileria lestoquardi in Tunisia by Rjeibi et al in 2016. Hyalomma anatolicum was reported to be found in Iran at a rate of 38.83% (Biglari et al, 2018). In Iraq, 50 ticks collected from cows were characterised by PCR, the result showed the presence of Hyalomma anatolicum (Al-Fatlawi et al, 2018). In Turkey, a study by Aktas showed that 2895 ticks were identi ed as Hyalomma anatolicum and that 11.3% of male ticks and 22.4% of female ticks were positive in Theileria (Aktas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular study of the tick Hyalomma anatolicum in Iraq have been recorded this spp. in Najaf city (5). The severity of clinical signs of tropical theileriosis depends on the type of animal breeds and on the age of animals; however, and the most common signs are anorexia, high body temperature, superficial lymph node enlargement (especially the prescapular, submandibular, and pre-femoral lymph nodes), pale of mucus membranes at early stages followed by an icteration at the late stages, uncommon blood-stained diarrhea, dehydration, salivation, lacrimation, nasal discharge, nervous signs, and dyspnea (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The classical methods for the diagnosis of theileriosis depend on using microscopy involving lymph and blood smears stained by Giemsa stain for checking the presence of Koch's bodies and the piroplasm (8). Many problems were shown due to the use of the smear methods that reflect low sensitivity for the diagnosis of carrier animals (9).…”
Section: Introductionmentioning
confidence: 99%